2021
DOI: 10.1002/ejoc.202001582
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptive Resorcinarene Hemicarcerand

Abstract: A new resorcinarene‐based hemicarcerand was developed, exhibiting pronounced flexibility in size and shape to accommodate several guest molecules. With a series of seven hemicarceplexes, investigated via single‐crystal XRD, the cage molecule showed to align its guests to complement their electrostatic potentials and to adjust its dimensions, according to the guest molecule‘s demand. Though forming equimolar inclusion complexes with most guests, crystallization from chloroform, and benzonitrile produced hemicar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…51 Ward et al reported a cubic coordination cage with packing coefficients of up to 87%, 52 while Dyker et al reported an adaptive resorcinarene hemicarcerand with packing coefficients as high as 91%. 53 In this study, SC4H exhibited the highest PC (over 100%) to fit the cavity of 1•(PF 6 ) 4 , with only the lower rim capable of sliding into the macrocycle.…”
Section: Discussionmentioning
confidence: 54%
“…51 Ward et al reported a cubic coordination cage with packing coefficients of up to 87%, 52 while Dyker et al reported an adaptive resorcinarene hemicarcerand with packing coefficients as high as 91%. 53 In this study, SC4H exhibited the highest PC (over 100%) to fit the cavity of 1•(PF 6 ) 4 , with only the lower rim capable of sliding into the macrocycle.…”
Section: Discussionmentioning
confidence: 54%
“…Bottom left to right: benzaldehyde (CCDC: 2047582), nitrobenzene (CCDC: 2047576), benzonitrile (CCDC: 2047580), chloroform (CCDC: 2047579). Comparison of calculated cavities . CCDC: Cambridge Crystallographic Data Centre numbers.…”
Section: Cages and Containers Soluble In Organic Solvents And Their A...mentioning
confidence: 94%
“…By way of example, the volume of the cavity in 116 changes from 197 to 154 Å 3 when toluene and chloroform guests are, respectively, encapsulated (Figure 37). 102 Martı ́nez, Saaidi, and co-workers showed that subtle differences in the functional groups that envelope the cavity of cages 117 and 118 play a key role in defining affinity to encapsulate a certain guest. This is nicely demonstrated in the encapsulation of organochlorine insecticide chlordecone 119 by 117 and 118.…”
Section: Cavitands Hemicarcerands Carcerands and Cryptandsmentioning
confidence: 99%